KOLABORASI YANG DILAKSANAKAN DI KAWASAN WISATA DERMAGA KERENG BANGKIRAI KOTA PALANGKA RAYA - Setiawan, Ferry; Saefulloh, Ahmad (Administratio, 2019)
One of the tourist attraction locations in Palangka Raya City that can be seeded is the Kereng Bangkirai pier which is the entrance to the Sebangau National Park in the Village of Kereng Bangkirai, Sabangau District, Palangka Raya City. However, tourism activities need to involve many parties in order to improve people's welfare and sustainable development goals can be achieved.Thus, this study aims to find out the collaboration carried out by the government, the private sector and the community in developing tourism in the Kereng Bangkirai jetty in Palangka Raya City and proposes a government and private collaboration model suitable for tourism development in these locations. In addition, this study also identifies inhibiting factors and supports collaboration in the development of tourism in the Kereng Bangkirai jetty in Palangka Raya City.This research was conducted using descriptive qualitative research methods with data collection techniques through observation, interviews and documentation studies in the Tourism Region of the Kereng Bangkirai Pier Palangkaraya City. The data analysis technique used in this study is an analysis using an interactive model. The target and output of this research is a picture of collaboration carried out by the government, private sector and the community which can later be used as a basis for the city government to develop a tripartite collaboration model for tourism development in the Kereng Bangkirai pier area in Palangka Raya City. In addition, this research will also identify inhibiting factors and support collaboration and tourism management in tourism deals carried out in the development of tourism in the region.